Examining the Drivers of Perceived Value and Purchase Intention in the Halal Beauty Industry - Lucia Nurbani Kartika; Cheryl Marlitta Stefia (UPT Publikasi Ilmiah UNISBA, 2026)
Halal consumption increasingly involves emotional and moral considerations beyond functional value, particularly in the cosmetic product context. This study examines the effects of perceived value, with a specific focus on emotional value, on moral elevation and halal purchase intention. Using survey data analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM), the results show that emotional value has a strong and significant effect on halal purchase intention (β = 0.4075; t = 5.3532) and moral elevation (β = 0.5406; t = 7.5140). Moral elevation also significantly influences halal purchase intention (β = 0.3762; t = 4.5309). While perceived value positively affects moral elevation (β = 0.3511; t = 4.5465), its direct effect on halal purchase intention is not significant (t = 1.8818), indicating a mediated relationship. These findings suggest that emotional and moral mechanisms play a central role in halal consumer decision-making. The study contributes to the Theory of Planned Behavior by extending the attitudinal component to incorporate moral emotions, demonstrating moral elevation as a key affective–moral pathway linking value perceptions to behavioral intention. In addition, the results advance moral emotions literature by positioning moral elevation as an active mediator in ethical consumption rather than a mere emotional response. Academic and managerial implications for halal cosmetic marketing strategies are discussed.